2017
DOI: 10.1177/1548051817709007
|View full text |Cite
|
Sign up to set email alerts
|

Quitting the Boss? The Role of Manager Influence Tactics and Employee Emotional Engagement in Voluntary Turnover

Abstract: When I turned in my letter, [the manager] said he was surprised and wanted to know what it would take to make me stay," says Anna. "I said that the working conditions were not conducive to effective performance, because I couldn't say the truth-that he made us all miserable. So two days later, he comes back with a new offer. I could have more money or fewer hours, but nothing else was any different. It's still the same toxic atmosphere." (An employee discussing her resignation in Robinson, 2008, p. 1) Retainin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
68
3
3

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 80 publications
(77 citation statements)
references
References 92 publications
(217 reference statements)
3
68
3
3
Order By: Relevance
“…For several years, the focus of these efforts has been on how emotional exhaustion affected resource investment strategies tied to performance at work (Demerouti et al 2014, Halbesleben & Bowler 2007, Wright & Cropanzano 1998. More recent work has started to expand that body of work into other realms of job performance (Park et al 2014), also exploring such outcomes as absenteeism (van Woerkom et al 2016), turnover (Marchand & Vandenberghe 2016, Reina et al 2017, and safety behaviors (Halbesleben 2010).…”
Section: Moving Beyond Stressmentioning
confidence: 99%
See 1 more Smart Citation
“…For several years, the focus of these efforts has been on how emotional exhaustion affected resource investment strategies tied to performance at work (Demerouti et al 2014, Halbesleben & Bowler 2007, Wright & Cropanzano 1998. More recent work has started to expand that body of work into other realms of job performance (Park et al 2014), also exploring such outcomes as absenteeism (van Woerkom et al 2016), turnover (Marchand & Vandenberghe 2016, Reina et al 2017, and safety behaviors (Halbesleben 2010).…”
Section: Moving Beyond Stressmentioning
confidence: 99%
“…On the other end of the spectrum, researchers have increasingly explored the impact that resources play in shorter-term settings, such as across days or weeks (Demerouti et al 2015, Donald et al 2016, Rodríguez-Muñoz et al 2017. Within that line of work are studies more closely examining the importance of how individuals spend their time in terms of the resources they gain or lose (Halbesleben et al 2013, Hunter & Wu 2016, Zacher et al 2014.…”
Section: The Role Of Timementioning
confidence: 99%
“…For example, previous research has found that when individuals gain resources at work, they are more likely to have high levels of well‐being (Hobfoll, ) and job performance (Park, O'Rourke, & O'Brien, ). However, resource depletion constitutes a threatening and stressful situation, which is associated with individuals' emotional exhaustion (Lapointe, Vandenberghe, & Panaccio, ), burnout (Halbesleben, ), and turnover (Marchand & Vandenberghe, ; Reina, Rogers, Peterson, Byron, & Hom, ). In the current study, we expect that managerial coaching is one such behavior that could generate new resources, and meanwhile, consume current resources for managers doing the coaching.…”
Section: Theoretical Background and Development Of Hypothesesmentioning
confidence: 99%
“…Firms should examine their company procedures concerning organizational and interpersonal justice to assess how their employees are treated and evaluated by both the company and management in an effort to reduce turnover (Flint et al, 2013). The use of pressure tactics by management within a firm are often correlated with employee turnover, with last-second appeals by managers who employ a pressure approach to retain personnel rendered ineffective (Reina, Rogers, Peterson, Byron & Hom, 2018). According to Shuck, Twyford, Reio, and Shuck.…”
Section: General Costs Of Employee Turnovermentioning
confidence: 99%